Motivation and Learning Achievement of Primary Students in Theme-Based Learning using Blended Learning Model (Universitas Negeri Semarang, 2018)
The purpose of this research is to improve motivation and learning achievment of students in theme-based learning using blended learning model in primary schools. This type of research is mixed methods, with the design of embedded experimental models. The mixed methods model consist of three phase. They are pre-intervention, during an intervention, and after intervention. Those phase pre-intervention, interviews with the class teacher, surveys, given the motivation questionnaire, and pre-tests. Then the intervention of theme-based learning using a blended learning model, observation for learning. Then the after-intervention, given the post-test, motivation questionnaire and response after learning implementation. To gain the quantitative data to strengthen the quantitative data the student's response, then focus group discussion (FGD) was implemented. Final interpretation of the data based on quantitative and qualitative data. Data were analyzed using the Wilcoxon Rank and triangulated whit the quantitative. The sample of the study was 113. The data collection was conducted by questionnaire, interviews, and documentation. Results of this study was an increase in motivation and learning achievement significantly. This is evident by the analysis of statistical tests obtained an average increase of 56.50 learning motivation and learning achievement at 57.00. Base on the data analysis can be concluded is an improvment increase in motivation and learning achievement of students after following theme-based learning using blended learning. Students were also responding very well to the learning. Thus the theme-based learning using a blended learning model in primary schools are very effective and recommended for in primary schools especially upper-grade students.